Herbicidal and Antibacterial Secondary Metabolites Isolated from the Nicotiana tabacum-Derived Endophytic Fungus Aspergillus japonicus TE-739D - Haisu Wang; Xiaolong Yuan; Xinrong Huang; Peng Zhang; Gan Gu (Plants)
Endophytic fungi possess a unique ability to produce abundant secondary metabolites, which play an active role in the growth and development of host plants. In this study, chemical investigations on the endophytic fungus Aspergillus japonicus TE-739D derived from the cultivated tobacco (Nicotiana tabacum L.) afforded two new polyketide derivatives, namely japoniones A (1) and B (2), as well as four previously reported compounds 3–6. Their chemical structures were elucidated by detailed spectroscopic analyses and quantum chemical calculations. In the herbicidal assays on the germination and radicle growth of Amaranthus retroflexus L. and Eleusine indica seeds, compound 1 was found to inhibit the germ and radicle elongation. Notably, compound 2 showed potent herbicidal activity against A. retroflexus L. germ elongation, with an IC50 value of 43.6 μg/mL, even higher than the positive control glyphosate (IC50 = 76.0 μg/mL). Moreover, compound 4 demonstrated strong antibacterial effects against the pathogens Bacillus cereus and Bacillus subtilis, with a comparable MIC value of 16 μg/mL to the positive control chloramphenicol. These findings indicate that the endophytic fungus A. japonicus TE-739D holds significant metabolic potential to produce bioactive secondary metabolites, which are beneficial, providing survival value to the host plants.